2016
DOI: 10.1152/ajpregu.00057.2015
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose tissue is involved in the seasonal variation of cold-induced thermogenesis in humans

Abstract: Brown adipose tissue (BAT) contributes to whole-body energy expenditure (EE), especially cold-induced thermogenesis (CIT), in humans. Although it is known that EE and CIT vary seasonally, their relationship with BAT has not been investigated. In the present study, we examined the impact of BAT on seasonal variations of EE/CIT and thermal responses to cold exposure in a randomized crossover design. Forty-five healthy male volunteers participated, and their BAT was assessed by positron emission tomography and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 55 publications
7
73
0
Order By: Relevance
“…Recent research reports that the change in skin temperature of the supraclavicular area (ΔSCV) after a cooling condition can act as an indirect biomarker of BAT thermogenesis (Boon et al, ; Chondronikola et al, ; Salem et al, ; van der Lans et al, ; Yoneshiro et al, ). In response to cold stress, BAT deposits within the neck are activated by norepinephrine, which warms the skin above the clavicle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research reports that the change in skin temperature of the supraclavicular area (ΔSCV) after a cooling condition can act as an indirect biomarker of BAT thermogenesis (Boon et al, ; Chondronikola et al, ; Salem et al, ; van der Lans et al, ; Yoneshiro et al, ). In response to cold stress, BAT deposits within the neck are activated by norepinephrine, which warms the skin above the clavicle.…”
Section: Introductionmentioning
confidence: 99%
“…In response to cold stress, BAT deposits within the neck are activated by norepinephrine, which warms the skin above the clavicle. Adults with active supraclavicular BAT exhibit either a minimal decline or an increase in skin temperature—ranging between −0.9°C and + 0.3°C—depending on the time length and severity of cooling condition (Boon et al, ; Chondronikola et al, ; Salem et al, ; van der Lans et al, ; Yoneshiro et al, ). In comparison, adults without detectable supraclavicular BAT experience a decline in skin temperature of around −1.5°C in this area (Chondronikola et al, ; Yoneshiro et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…). Numerous studies showed that the effects of chronic cold exposure are compelling and significantly improve systemic metabolic homeostasis, including insulin sensitivity as well as glucose and lipid profiles . Nevertheless, results of adult human‐based studies revealed important discrepancies, perhaps due to varying study conditions and experimental designs .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the peripheral tissues, the temperature of the brain is an input into the thermoregulatory system . One of the hypotheses explaining why human BAT is placed in the cervical and supraclavicular zone is that, as a thermogenic tissue, its main function is to regulate the temperature of the blood going to the brain . Several studies have shown that human BAT activation is related to an increase in the blood flow in BAT .…”
Section: Discussionmentioning
confidence: 99%